Model Optimisasi Diskrit untuk Perencanaan Sistem Logistik Terpadu: Model Optimisasi Sistem Logistik Terpadu - Joni Mulyasri (Jurnal Analisis Riset, Statistik dan Komputasi, 2023)
Planning the right Supply Chain Management (SCM) horizon in designing an integrated logistics network model and optimizing all factors that affect the production distribution process in a multi-echelon supply chain and helping companies to remain competitive in this turbulent economy and able to survive in an era of disruption that does not unexpected in the era of the industrial revolution 4.0. The supply chain network is defined as a network that performs business functions to obtain materials, transform materials into intermediate products and final products, and distribute various company product results from distribution centers to consumer demand zones through distribution in a unified multi-echelon inventory system. The proposed model uses the Mathematical Mixed Integer Non-Linear Programming (MINLP) approach. The proposed model is to help select the direct feasibility search algorithm (Neighborhood Search) from each distribution center (DC) to plan the design of a multi-echelon supply chain network structure, transportation, inventory, and distribution of production results to a distribution center in an integrated logistics system so that it can minimize the total logistics costs that will have an impact on the profitability of a company.